Agadirius trojani gen. et sp. nov.: a new owlfly (Neuroptera: Ascalaphidae) from Morocco - Badano, Davide; Pantaleoni, Roberto Antonio (Zootaxa, 2012)
A new owlfly, Agadirius trojani gen. et sp. nov., (Ascalaphidae: Ascalaphinae), is described from the Anti–AtlasMountains, Morocco. The habitus is unmistakable and differs from all other owlflies, but shares some superficial featureswith the genus Puer Lefèbvre, 1842. Agadirius gen. nov., belongs to the subfamily Ascalaphinae (split eyed owlflies) and has genitalia consistent with the tribe Ascalaphini as defined by Tjeder and Hansson (1992).